INFORMATION AND COMMUNICATION TECHNOLOGY (ICT) ORIENTED TASK IN ENGLISH TEXTBOOKS - hendi hidayat; linda silfiyana (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2018)
As the world changed into the digital era, it surely affected the educational field where the curriculum also developed. The latest curriculum used in Indonesia called as Curriculum 2013 (Kurtilas) which was the product of a long discussion within the ministry demanded the integration of Information and Communication Technology (ICT) in educational field. This study was intended to explore the implementation of Curriculum 2013 (Kurtilas) in the aspect of Mindset Refinement where isolated teaching and learning system was changed into learning in a networking way in which learners can gain knowledge from anyone and from anywhere that could be reached and obtained through the use of technology. This study analyzed ICT-oriented tasks reflected in two English textbooks. Qualitative study is conducted to analyze the skill focus, hardware used, software used, and activity types found in both English textbooks through document analysis. The result shows that both books were different in developing skill focus when formulating ICT oriented task in which one of them was only focusing on the speaking and writing skills. The use of hardware was mostly centered on computing and communication equipments. In case of the software used, the result showed that both books mainly focussed on the use of office and multimedia software. Both English textbooks were different in the frequency of the software used for assisting students in doing ICT oriented tasks as the differences between both textbooks in formulating the activity types.